Problems of Execution and Implementation of Arbitration Decisions in Settling Workers' Rights Disputes - Nikmah Dalimunthe; Siti Nazua Novianti (Jurnal Sahabat ISNU SU, 2024)
Arbitration, as an alternative mechanism for resolving workers' rights disputes, should offer legal certainty that is faster and more efficient than conventional litigation. However, in practice, arbitration awards, which are normatively final and binding, often face serious obstacles at the execution and implementation stages. This study critically analyzes the problems of executing arbitration awards in the context of workers' rights disputes in Indonesia, identifies legal loopholes exploited by losing parties to delay or thwart the implementation of the award, and examines their impact on the fulfillment of workers' normative rights. Using a normative juridical approach with comparative analysis and case studies, the study finds that weak execution mechanisms, multiple interpretations of public order provisions, and procedural gaps in filing applications for annulment of awards are the main root causes of the problem. Substantive reforms in labor arbitration regulations, strengthening the capacity of arbitration institutions, and stricter mechanisms for monitoring execution are absolutely necessary.